Sosialisasi rintisan pengembangan desa wisata kebugaran kelurahan Canden kabupaten Bantul D.I Yogyakarta - Helfi Agustin; M. Syamsu Hidayat; Wardiyanta Wardiyanta; Fitroh Adhilla (INDRA: Jurnal Pengabdian kepada Masyarakat, 2023)
Canden, a village in the Bantul Regency, is one of the tourism settlements with the potential to develop. The village of Canden comprises 15 hamlets, one of which is Kiringan, recognized as a hub for conventional herbal medicine. This hamlet is home to at least 110 herbal medicine vendors. This community service project aimed to make it easier for the town of Canden to thrive as a tourism destination, starting with the potential of herbal medicine as the foundation of wellness travel. This community service approach was participatory rural appraissal using  focus group discussion with community, tourism management, head of the tourism office, public health center,  university, and so on.  This community service was carried out smoothly and the results were obtained in the form of community mapping and identification of needs in the development of fitness tourism villages.